Design And Implementation Of Smart Home Automation And Security System - Ibrahim , Mohd Zulfadli (UTeM, 2008)
This project is about the design and implementation of Smart Home Automation and Security System. It comprises of integration between Programmable Logic Controller (PLC), PIC Programming Controller, Global System Mobile (GSM) mobile communication, home automation, and security system. This project consists of Security Door Access, Security System Using GSM Controller, Home Appliances using GSM Controller, and Automatic Watering System. This combination of technology will produce a home automation called Smart Home System. Smart Home is an integration of various systems at home which is coordinated by Smart Home controller and controlled by users using command interfaces while security system is an electrical device that sets off an alarm when someone tries to break in. This project can be divided into two main parts which are hardware and software development. The hardware development includes the PLC wiring connection, PIC interfacing circuit, relay connection and home automation circuit. The software development includes develop the PLC ladder diagram, PIC controller source code, GSM message command, and relay diagram. This system is controlled by users using 6 various centralized command interfaces such as hand phone, personal digital assistants (PDA), keypad and switches.